Indicadores de sustentabilidade : subsídios para o gerenciamento da logística reversa de pós-consumo de pneus inservíveis no município de Aracaju/SE - Leite, Danielle Thaís Barros de Souza (2017)
The increasing quantity of post-consumer products results in pollution and excess waste. In order to reduce this impact, environmental legislation related to the issue gradually releases governments and holds private companies accountable for the management of reverse flows of post-consumer products. Logistics involves the process that makes products reach into the hands of the end consumer as well as the return. In the automobile market, the manufacturer is responsible for the production chain and for the recycling of its components. Due to legal requirements, the various actors in the production chain seek to operate in the automotive tire reverse post-consumer logistics chain and its management. The Solid Waste Act establishes that manufacturers, distributors and traders are obliged to take care of the collection and destination for recycling. Post-consumer reverse logistics for automotive tires is important for sustainability because it provides benefits to companies, society and the environment. Based on the foregoing, this research had as general objective to analyze the environmental, social and economic sustainability of the reverse logistics of post-consumption of waste tires in Aracaju / SE, aiming to subsidize the management of waste tires through indicators, a tool used to generate a index to measure the sustainability of the system being analyzed. Regarding the paradigm, the present research is classified as critical. This thesis has an applied and pragmatic nature, since it seeks political solution at the level of public policies, changes in consumer behavior and recycling. It is a survey of indicators and descriptive indexes. The characterization of the productive chain of waste tires in Aracaju / SE was carried out and a matrix of sustainability indicators was constructed based on the DPSIR method. Sustainability indicators were measured and a scale was developed to create a sustainability index. The environmental, social and economic sustainability indexes were classified as poor in the proposed scale, which proves that the chain of reverse logistics management of waste tires in Aracaju does not meet the sustainability assumptions. Thus, the problem of the negative externality of waste tires is an exercise of neoclassical economics, does not solve the problem of sustainable disposal, however the reverse logistics when it comes to the internalization of this externality gave economic visibility, which would be a cost of opportunity to recycle in Aracaju. In this way, it was proposed to propose actions aimed at assisting in the management and final destination of tires in the reverse logistics chain, contributing with future research, which could be used in the integrated management and environmentally sound management of solid waste. Other products subject to reverse logistics.